2009
DOI: 10.1134/s0006297909090120
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-induced programmed cell death in plants

Abstract: Chitosan, CN(-), or H(2)O(2) caused the death of epidermal cells (EC) in the epidermis of pea leaves that was detected by monitoring the destruction of cell nuclei; chitosan induced chromatin condensation and marginalization followed by the destruction of EC nuclei and subsequent internucleosomal DNA fragmentation. Chitosan did not affect stoma guard cells (GC). Anaerobic conditions prevented the chitosan-induced destruction of EC nuclei. The antioxidants nitroblue tetrazolium or mannitol suppressed the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…For the chitosan as a stimulant, chitosan is known to elicit activities leading to a variety of defensive responses in host plants to microbial infections, including the accumulation of phytoalexins, pathogen related proteins, callus formation and accumulation of secondary metabolite (Yin et al, 2012). This study found that the most effectivechitosan concentrations for inducing vinblastine and vincristine in C. roseus cell culture were 100 to 250 mg/L because itinduced programmed cell death and hypersensitive-associated responses in plants cell when concentration increased (Vasil'ev et al, 2009) or chitosan toxicity to the living cells or might be due to the phytotoxic action of vinblastine and vincristine on the cells (Amborabé et al, 2008). These results also agreed with the studies in Plumbago indica root cultures of Jaisi and Panichayupakaranant (2016).…”
Section: Discussionmentioning
confidence: 85%
“…For the chitosan as a stimulant, chitosan is known to elicit activities leading to a variety of defensive responses in host plants to microbial infections, including the accumulation of phytoalexins, pathogen related proteins, callus formation and accumulation of secondary metabolite (Yin et al, 2012). This study found that the most effectivechitosan concentrations for inducing vinblastine and vincristine in C. roseus cell culture were 100 to 250 mg/L because itinduced programmed cell death and hypersensitive-associated responses in plants cell when concentration increased (Vasil'ev et al, 2009) or chitosan toxicity to the living cells or might be due to the phytotoxic action of vinblastine and vincristine on the cells (Amborabé et al, 2008). These results also agreed with the studies in Plumbago indica root cultures of Jaisi and Panichayupakaranant (2016).…”
Section: Discussionmentioning
confidence: 85%
“…High doses of this polymer induce peroxidase and polyphenol oxidases, which in turn generate phenolic compounds 3 and calose depositions 52 in plant cells. Chitosan also triggers induction of programed-cell death (PCD) in plants 53 . The involvement of PCD in the inhibitory effect of chitosan on root development should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied plant responses to chitosan treatment are the formation of chemical and mechanical barriers and the synthesis of new molecules and enzymes involved in the defence response [15,37]. In some cases, chitosan causes the induction of the hypersensitive response, mainly around the infection site, that leads to the programmed cell death [44]. This hypersensitive response can be followed by systemic response of the plant defence mechanisms.…”
Section: Plant Resistance Elicitationmentioning
confidence: 99%